Development of a Berberine Loaded Multifunctional Design for the Treatment of Helicobacter pylori Induced Gastric Ulcer - Jain, Sunil K.; Patel, Kamlesh; Rajpoot, Kuldeep; Jain, Akhlesh (Drug Delivery Letters, 2019)
Background and Objective: The H. pylori infection causes chronic inflammation and significantly increases the risk of developing duodenal and gastric ulcer disease and gastric cancer. Infection with H. pylori is the well-known risk factor for gastric cancer. It is highly desirable to develop a delivery system that localizes the antibiotic at the site of infection to achieve bactericidal concentration for a longer period of time. Thus, present work aimed to develop Concanavalin-A (Con-A) conjugated gastro-retentive microspheres of polymethylmethacrylate (PMMA) and polyethylene oxide (PEO) containing berberine hydrochloride (BBR) for the treatment of H. pylori infection. Methods: Microspheres were prepared by solvent evaporation method and characterized by particles size distribution, surface morphology, % drug entrapment and in vitro drug release in the simulated gastric fluid. Optimized microspheres were conjugated with Con-A and further characterized for Con-A conjugation efficiency, in vitro drug release and ex vivo mucoadhesive properties. Results and Conclusion: Enhanced mucoadhesion (88±1.9%) was shown by Con-A conjugated microspheres as compared with non-conjugated microspheres (14.5±3.6%). This significant difference (p<0.05) in the mucoadhesion may be due to affinity of the Con-A towards glycoproteins of mucus membrane of stomach. Attachment of lectin (Con-A) to the microspheres significantly enhanced the mucoadhesiveness as well as also controlled the berberine release for 10 h study period. The preliminary results from this study advised that Con-A conjugated PMMA and PEO microspheres could be used to incorporate some more herbal drugs and may be used for oral administration against H. pylori in the stomach.
Keywords: polyethylene oxide